Digital Transformation in Operations Management: Leveraging Technology to Improve Business Efficiency - Desman Serius Nazara; Agung Sutrisno; Nersiwad; Mohammad Muslimin (Maneggio, 2024)
Digital transformation in operations management has become an urgent need for companies to improve efficiency, productivity, and competitiveness in the face of an increasingly complex and competitive business environment. Digital technologies such as the Internet of Things (IoT), artificial intelligence (AI), robotics, and big data provide opportunities for companies to optimize various aspects of operations. This article aims to explore how digital transformation can be applied in operations management to support these goals. The research method used is a literature review, where various previous studies and industry reports are analyzed to identify the benefits, challenges, and impacts of digital technology implementation on business operations. The results show that the implementation of digital technology enables companies to speed up workflows, reduce costs, improve process accuracy, and prepare the foundation for continuous innovation. In the discussion, it is also explained that although there are challenges in terms of investment costs, training, and data security, companies that successfully overcome these barriers will gain a significant competitive advantage. The implications of these findings are the importance of continued investment in technology and human capital development, as well as the adoption of sustainability strategies to support long-term growth.